Brief Report: Informing Strategies to Build PrEP Capacity Among San Francisco Bay Area Clinicians. (1st February 2017) - Bacon, Oliver; Gonzalez, Rafael; Andrew, Erin; Potter, Michael B.; Iñiguez, James R.; Cohen, Stephanie E.; Liu, Albert Y.; Fuchs, Jonathan D.
Abstract : Abstract: A large pool of clinicians are needed to meet the growing demand for HIV preexposure prophylaxis. We surveyed a mixed group of HIV specialists and nonspecialists in the San Francisco Bay Area to determine their attitudes toward and training needs regarding prescribing preexposure prophylaxis to persons at increased risk of HIV infection. Willingness to prescribe was associated with experience in caring for HIV-infected patients (adjusted odds ratio 4.76, 95% confidence interval: 1.43 to 15.76, P = 0.01). Desire for further training was associated with concerns about drug resistance ( P = 0.04) and side effects ( P = 0.04) and was more common among noninfectious disease specialists. Clinicians favored online and in-person training methods.